PENERAPAN STRATEGI MOTIVASI ARCS PADA MATERI MEMAHAMI UNSUR INTRINSIK NOVEL - Siti Kholifah (MEDIA DIDAKTIKA, 2016)
The purpose of this study is 1) to describe the activities of learners in the learning of the application of motivational strategies ARCS on the material listened to the intrinsic elements of the novel 2) describing the thoroughness of the study of students after application of motivational strategies ARCS on the material listened to the intrinsic elements of the novel 3) describe the response of learners after learning ARCS motivation towards the implementation of strategies to material intrinsic elements of the novel.This research is the application of motivational strategies ARCS, with qualitative method is descriptive based on data obtained from the results: Observations to determine the activities of learners (observation sheets) done observers in learning, test questions (essay as much as 7 for students), questionnaire (questionnaire response for students) after learning takes place, data sources totaling 28 students of class VIII A MTs Son-daughter Lamongan in the academic year 2015/2016. The results of data analysis based on data classification research activity of students in three meetings showed an average yield of 98.9% in the first meeting of KD 13.1, 97.4% in the second meeting of KD 13.2 and 98.5%, in the third meeting of KD 13.3. Obtaining an average of three meetings, 98.2% expressed very well. The study of students reached 85% and the student's response to the application of ARCS motivation strategy after learning takes to reach an average of 94.5% and is expressed very well.Based on the results of this study concluded that the implementation strategy ARCS motivation in understanding the intrinsic element of the novel material is effectively used and in the implementation of the application in the ARCS motivational strategies need to take into learning-hatikan allocation of time for the learning process goes according to destination.